Overview of Interest in Career Choice of Students Using the Rothwell Miller Interest Blank (RMIB) Test Approach - Tafui, Shaloom Anastasya; Lerik, Mariana Dinah Charlota; Weraman, Pius; Aipipidely, Diana (Universitas Nusa Cendana, 2025)
Abstract. This study aims to describe the career interests of students at SMAN Kapan using the Rothwell Miller Interest Blank (RMIB) Test approach. Interest is a stable tendency to focus and be attracted to certain activities without coercion. This research employed a descriptive quantitative approach with purposive sampling involving 62 twelfth-grade students. The data collection instrument was the RMIB Test, which includes 12 categories of interest. The results showed that the highest interest among male students was in the Mechanical category (26%), while female students were most interested in the Aesthetic category (20%). The lowest interest was found in the Social Service category (3.2%). These findings highlight the importance of psychological tools, such as the RMIB test, in identifying students' interests as a foundation for appropriate career decision-making. This research is expected to assist students, schools, and parents in developing more targeted and potential-based career planning. Keywords: interest, career choice, RMIB test, high school students, educational psychology